Exploring the nutraceutical elixirs of commercial fruit and vegetables and wild edible plants with ethnomedicinal importance: Review article - Jacob, Sharon; Raj, Anupam; Gomez, Saji (International journal of health sciences, 2024)
The increasing emphasis on preventive healthcare has sparked interest in nutraceuticals, which bridge the gap between nutrition and pharmaceuticals. Nutraceuticals, including functional foods, supplements, and herbal products, are gaining popularity for their targeted health benefits, reflecting a societal shift towards proactive health management. Defined by the Food Safety and Standards Authority of India, nutraceuticals provide health benefits beyond basic nutrition and are increasingly valued for their preventive and therapeutic properties. This review explores the nutraceutical potential of fruits, vegetables, and wild edible plants, highlighting their diverse bioactive compounds. Fruits and vegetables are rich in phytochemicals like minerals, vitamins, dietary fiber, and bioactive compounds such as flavonoids, contributing to their nutraceutical potential. Focusing on fruits like mango, pineapple, citrus, and berries like strawberry and blueberry, the discussion underscores their role in enhancing overall well-being. Studies on specific vegetables such as tomato, garlic, moringa, etc., highlight their diverse health benefits, including antioxidant and anti-inflammatory properties. Research on wild edible fruits and vegetables among tribal populations in India reveals their nutritional and therapeutic significance, providing insights into their ethnomedicinal uses.